Tiger Grouper seeds "infected" with parasites: Obstacles and Impacts - Hendarto, Totok; Dhakal, Herman; Labh, Sharma (Assyfa Journal Scientific Essay, 2024)
The future significance of mariculture development in Indonesia lies in its potential to enhance the growth of the fisheries subsector. The fisheries subsector is anticipated to prioritize and serve as a potential catalyst for economic expansion. The cultivation of tiger grouper among marine fish exhibits significant potential for advancement. Nevertheless, the primary impediment to expanding aquaculture production, whether conducted intensively or extensively, is the occurrence of disease and pest outbreaks among fish populations. Fish sickness is a significant contributor to economic losses within the society, particularly among farmers who rely on the cultivation of tiger grouper (Ephinephelus fuscoguttatus) as a valuable commodity. One of the challenges encountered in cultivating groupers pertains to the elevated mortality rate. The presence of the disease poses a significant obstacle to the successful production of grouper. The present study investigates the parasitic infections observed in tiger grouper (Ephinephelus fuscoguttatus). The present study was undertaken by comprehensively evaluating relevant literature published in the past decade, spanning 2013 to 2023. Seven studies about this subject were identified utilizing Harzing's Publish or Perish program. The findings indicate that a particular parasite species, Diplectanum sp., was identified in tiger grouper (Ephinephelus fuscoguttatus). Additional parasites are present and will be examined in this paper.